Investigation of optical parameters of boron doped aluminium nitride films grown on diamond using spectroscopic ellipsometry. (5th December 2014) - Xie, Deng; Qiu, Zhi Ren; Talwar, Devki N.; Liu, Yi; Song, Jen–Hao; Huang, Jow–Lay; Mei, Ting; Liu, Chee Wee; Fang, Zhe Chuan
Boron doped aluminium nitride (B)AlN films are prepared on diamond substrate by using a co–sputtering system. The dielectric function of diamond substrate and (B)AlN films with B contents of 0%, 3%, 5% are extracted by using the spectroscopic ellipsometry. Whereas the (B)AlN films having B contents lower than 5% are considered important for improving crystalline and electronic properties of the buffer layers - the films with B contents ≤3%, however, do not cause appreciable changes in its direct bandgaps.